An analysis of merger and amalgamation transactions under the Companies Act 71 of 2008 and the Income Tax Act 58 of 1962 - Meyer, Carolina (University of Pretoria, 2023)
In law it is common to encounter two separate pieces of legislation which govern a single matter or transaction, for example, the Companies Act 71 of 2008 (the Companies Act) and the Securities Transfer Act 25 of 2007 both of which address the sale of shares. Similarly, the Income Tax Act 58 of 1962 (the Income Tax Act) and the Companies Act both have regulations which govern, respectively, tax law and company law matters in South Africa. These two Acts overlap in various business and commercial fields as tax is frequently an important component of any business transaction undertaken by a company. Issues, however, arise when the regulations in these two Acts, are inconsistent. This can be observed if one compares the current South African Income Tax and Companies Act, specifically as regards the sections involving merger and amalgamation transactions. Section 44 of the Income Tax Act governs merger and amalgamation transactions from a tax perspective and provides for tax rollover relief if certain requirements are met. The regulations governing mergers and amalgamations under the Companies Act are contained in sections 113, 115 and 116 of the Act. Although these sections in both Acts address the same transaction – a merger or amalgamation between two or more companies – there are several discrepancies between the regulations in the two Acts which appear to operate entirely independently of one another. In practice, one often sees that other sections in the Companies Act and Income Tax Act are used to achieve a merger due, in the main, to the uncertainties in the application of the relevant merger sections in the two Acts and the limited interaction between them. This study identifies and assesses the impact of the discrepancies identified in these two Acts in relation to merger and amalgamation transactions. The study makes recommendations to address these discrepancies and to align the South African Companies Act and Income Tax Act as regards merger/amalgamation transactions.
URI: https://repository.up.ac.za/handle/2263/94064
Keywords: Amalgamation; Companies Act; Income Tax Act; Merger; Taxation

مدى تأثر الشركة بانسحاب الشريك (دراسة مقارنة) - شريفي, ويزة (جامعة مولود معمري, 2023)
تهدف دراسة موضوع انسحاب الشريك في القانون الجزائري والقانون المقارن إلى تحديد التنظيم القانوني لعملية انسحاب الشريك من الشركة، والوقوف على أسباب ومبررات عملية الانسحاب، وأهم الوسائل المتاحة لتحقيقه، خاصة وأنّ آثار الانسحاب تنصرف أساسا إلى الشريك المنسحب، كما تمتدإلى الشركة والشركاء والغير الذي تعامل مع الشركة. وقد أثبتت الدراسة المقارنة في القانونين الجزائري والفرنسي، مدى تأثر القانون الجزائري بالقانون الفرنسي، بسبب غياب تنظيم قانوني خاص في التشريع الجزائري لمسالة انسحاب الشريك من الشركة. ونتيجة لهذا الفراغ القانوني، استوجب الرجوع إلى القواعد العامة في القانون المدني، الذي ينظم عقد الشركة بصفة عامة، مع الأخذ بعين الاعتبار خصوصية الشركات التجارية والأحكام الخاصة المنظمة لها. إنّ انسحاب الشريك، قد يكون إراديًا في حالة قيامه بالتخلّي عن حقوقه الاجتماعية في الشركة، وقد يكون الانسحاب لا إراديا، عندما يكون عن طريق حكم قضائي، بحيث يتم في هذه الحالة إنهاء مهام الشريك من دون إرادته. وكقاعدة عامة، فإن انسحاب الشريك يِؤدي حتما إلى انقضاء الشركة، لاسيما إذا تعلق الأمر بشركات الأشخاص، إلا إذا كانت القوانين الأساسية للشركة والشركاء الباقون، قد قرروا خلاف ذلك، بمعنى استمرار الشركة. L’étude du retrait de l’associé en droit algérien et droit comparé a pour but de déterminer la réglementation juridique du mécanisme du retrait de l’associé de la société, afin de mettre l’accent sur les motifs du retrait, les moyens et techniques juridiques pour y parvenir, mais surtout ses effets, car le retrait touche principalement les droits de l’associé, les partenaires associés, et enfin les tiers. L’étude comparative du droit algérien et français, réaffirme l’influence du droit algérien par le droit français en raison de l’absence d’une règlementation spécifique relative au droit de retrait de l’associé. En raison de ce vide juridique, il est nécessaire de se référer aux règles générales du droit civil qui régissent le contrat de société, tout en tenant compte des spécificités des différents types de sociétés commerciales et des textes qui les régissent. Il est à préciser, que le retrait de l’associé peut être volontaire suite à sa renonciation à ses droits sociaux, mais il peut être involontaire dans le cas du retrait judicaire, quand il s’agit de mettre fin de manière unilatérale aux fonctions de l’associé. En règle générale, le retrait de l’associé entraine obligatoirement la dissolution de la société, notamment dans le cas des sociétés de personnes, sauf si les statuts de la société ou les associés ont convenus autrement, c’est à dire de la continuité de la société.
Keywords: Associés; Droit algérien; Droit comparé; Liquidation; Retrait d'associé; Scission; Société; التصفية; الشركاء; الشركة; القانون الجزائري; القانون المقارن; القسمة; انسحاب الشريك

أحكام التنازل عن الحصص وانتقالها في الشركة ذات المسؤولية المحدودة - بشيخ, ام الخير (Ibn Khaldun University of Tiaret, 2023)
المبدأ العام في الشركة ذات المسؤولية المحدودة هو تقييد التنازل عن الحصص، إذ لا يجوز التنازل عن الحصص إلى الغير إلا بموافقة أغلبية الشركاء الحائزين لثلاثة أرباع رأس المال. وهو ما نصت علية المادة571 من القانون التجاري. والاستثناء حرية التنازل عن الحصص إلى الأصول والفروع والأزواج مالم ينص القانون الأساسي على تقييد التنازل. كما يخضع فيها التنازل عن الحصص للاسترداد وهو حق مقرر لمصلحة الشركاء والشركة لشراء الحصص المرغوب في التنازل عنها في حالة رفض الموافقة على المتنازل إليه. وإذا كان الأصل العام في الشركة ذات المسؤولية المحدودة هو تقييد التنازل عن الحصص، فإن الحصص في هذه الشركة تنتقل بكل حرية إلى ورثة الشريك، بشرط أن لا يترتب على ذلك زيادة عدد الشركاء عن الحد الأقصى المقرر قانونا والذي هو 50 شريكا. ومع ذلك يمكن للشركاء تقييد انتقال الحصص إلى الورثة بشرط أن يتم إدراج هذا الشرط في القانون الأساسي للشركة. The general principle in a limited liability company is to restrict the assignment/ abdication of shares, as it is not permissible to assign shares to third parties except with the share-holders majority’s approval who possess three-quarters of the capital. This is what is stipulated in Article 571 of the Commercial Law. The exception is the freedom to assign/transfer shares to ascendants, descendants, and spouses, unless the Basic Law stipulates a restriction of abdication. In addition, the assignment of shares is subject to recovery, which is a right established in the interest of the partners and the company to purchase the desired shares to be assigned in the event of refusal to approve the assignee. Therefore if the general principle in the limited liability company is to restrict the abdication from shares, then the shares in this company are transferred freely to the partner’s heirs, provided that this does not result in an increase in the number of partners beyond the legally prescribed maximum, which are 50 partners. However, the partners can restrict the transfer of shares to the heirs, provided that this condition is included in the articles of association of the company.
Keywords: Associés; Cession d'actions; Droit de rachat; Offre d'actions; Société à responsabilité limitée

La protection des actionnaires minoritaires des sociétés anonymes dans l'espace juridique OHADA - Oueina, Florent (Université de Perpignan Via Domitia, 2023)
Susceptible d'être lésés dans leurs droits représentés par les actions dont ils disposent, les minoritaires dans une société anonyme, ont besoin d'être protégés « non parce qu'ils sont minoritaires, mais parce que leurs intérêts apparaissent comme dignes de protection ». Il n'est pas rare dans le cadre du fonctionnement de la société anonyme d'assister à la prise de décisions contraires, non seulement à l'intérêt des minoritaires, mais également à l'intérêt social, par les actionnaires majoritaires dans l'unique dessein de satisfaire les membres de la majorité au détriment des autres actionnaires. Cette tendance à l'écrasement des minoritaires entraîne des conflits, sinon des oppositions entre actionnaires conduisant à la constitution de blocs antagonistes dont l'attitude peut provoquer une crise au sein de la société. L'étude réside dans l'analyse des garanties et dans la recherche constante d'une protection efficace qu'offrent le législateur et l'autorité du marché financier aux investisseurs minoritaires dans l'espace OHADA. Cette étude étendue en droit français existe aussi en droit OHADA. Likely to be infringed in their rights represented by the actions at their disposal, minority shareholders in a public limited company need to be protected "not because they are in the minority, but because their interests appear to be worthy of protection". It is not uncommon in the context of the operation of the limited company to witness the taking of decisions contrary, not only to the interests of the minority shareholders, but also to the corporate interest, by the majority shareholders in the sole purpose of satisfying the members of the majority to the detriment of the other shareholders. This tendency to crush minorities leads to conflicts, if not oppositions between shareholders leading to the formation of antagonistic blocs whose attitude can provoke a crisis within society. The study lies in the analysis of guarantees and in the constant search for effective protection offered by the legislator and the financial market authority to minority investors in the OHADA area. This extended study in French law also exists in OHADA law.
Keywords: Actionnaire minoritaire; Company profits; Droit OHADA; Droit français; Droit à l'information; Intérêt social; Marché financier OHADA; Minority shareholder; OHADA Law and French Law; OHADA stock market; Public limited companies; Rights of information; S.A.; Société Anonyme

Liability in the atmosphere of groups of companies - Motassim, Sofia (Universitat de Barcelona, 2023)
Groups of companies are a complex corporate structure, whose regulation can be problematic, especially when it comes to liability. Indeed, liability within corporate groups draws forth a series of issues principally due to the principles of separate corporate personality and limited liability. In the context of limited liability, which is based on the notion of separate legal personality, the main issue waxes the protection of the creditors, in particular the creditors of the subsidiaries. One can find three regulatory templates for handling corporate groups and their liability: policing via general company and/or civil law (such as the English model); policing via special group legislation (such as the German model); and policing via branches of law such as insolvency law, antitrust law, and contract law, among others (which is the case in numerous jurisdictions, either coupled with the first or the second model). Lifting the corporate veil has come as an answer to corporate separateness, by permitting to ignore the shareholders’ limited liability and hold them personally liable for the debts of their companies in specific circumstances. However, one can hardly find cases in which the corporate veil has been successfully lifted, due to many factors. Other important questions that are posed in the scope of corporate groups liability are the parent company’s liability for the payment of its daughter companies’ debts when insolvency strikes and other respects, besides the matter of group liability. Furthermore, liability is as well a key player in terms of tort law, and corporate social responsibility has therefore found a place in the sun in the present climate.
Alternate link : https://diposit.ub.edu/bitstreams/83cde66e-b943-45b6-830b-831df41cb73f/download
Keywords: Ciències Jurídiques; Commercial law; Conglomerate corporations; Corporations; Derecho mercantil; Dret mercantil; Econòmiques i Socials; Grupos de empresas; Grups d'empreses; Liability (Law); Responsabilidad (Derecho); Responsabilitat (Dret); Sociedades; Societats

Mandatory Environmental, Social and Governance (ESG) Regulations: ESG Performance, Corporate Finance, and Investment - Michael, Emmanuel (Victoria University of Wellington, 2023)
This thesis investigates the relationship between cross-country mandatory environmental, social and governance (ESG) regulations and firm-level outcomes, such as ESG performance, corporate finance, and investment, for both developing and developed countries. ESG performance is initially examined to determine whether mandatory ESG regulations affect it and to what extent. Second, the study investigates the impact of mandatory ESG on corporate finance and investment. Lastly, the study explores whether mandatory ESG regulations affect firm-level outcomes based on countries' governance and economic systems, and industries. The study uses a large sample of 69,010 firm-years across 73 countries, over the period 2005 – 2020 to address the foregoing issues. In addressing the impact of mandatory ESG regulations on ESG performance, the study employs a difference-in-differences (DiD) design. The DiD technique can isolate the effect of regulatory shocks to firm-level outcomes. According to the DiD analysis conducted, cross-country mandatory ESG improves firm-level ESG performance in developed countries, but not in developing countries. The study also concludes that mandatory ESG regulations have a positive impact only on ESG components in developed countries and have a more dominant impact on environmental (E) component. The findings are robust to a range of checks and test cases, including a triple DiD design set-up and propensity score-matched sample. The study employs an investment Euler equation framework and generalised method of moments (GMM) estimators to explore how mandatory ESG impacts corporate finance and investment. Euler frameworks account for the dynamic nature of investment, whereas GMMs account for endogenous dynamics in dynamic models. The study demonstrates that mandatory ESG increases corporate investment by increasing firms' access to external funds. The findings are robust to a battery of tests, including a triple DiD design set-up, propensity score-matched sample and the parallel trends assumption. Using an investment Euler equation framework and the GMM estimators, the study explores whether the impact of mandatory ESG on corporate finance and investment is dependent on a country's governance and economic system. When mandatory ESG is affected by country factors such as governance systems and economic well-being, the effect of mandatory ESG on investment via internal finance channel persists, according to the study. However, while consistent results are found in developed countries, inconsistent results are found in developing countries. According to the study, oil, gas, and mining firms are likely to respond effectively to mandatory ESG regulations because of increased scrutiny and pressure. Overall, the findings from the study imply that cross-country mandatory ESG has had a positive impact on corporate ESG performance, finance, and investment. For firms located in developed countries, these findings hold consistently, while for those located in developing countries, the opposite holds true. Also, the study reveals that firms in the oil, gas, and mining industries effectively respond to regulatory requirements. As a result, this study provides policy makers and accountants with an understanding of how mandatory ESG impacts firm ESG activities and performance, which is crucial for regulatory reforms.
Keywords: Corporate Finance; Cross-Sectional Analysis; Developed countries; Developing countries; Economic Models and Forecasting; Finance; Financial Economics; Investment; Investment Euler equation; Mandatory ESG disclosure regulations; Panel Data Analysis; Sustainability Accounting and Reporting; Time-Series Analysis

The Double Life of State-Owned Enterprises in International Economic Law: States, Corporations or Both? - Kikarea, Eirini (University of Cambridge, 2023)
State-owned enterprises (SOEs) have recently gained prominence in global markets and feature among the world’s most influential enterprises. The aim of this research project is to analyse the international norms in force regulating whether SOEs are considered state or non- state actors, and their conduct state or non-state conduct, the interpretation and application of these norms by adjudicators in different international regimes, and to provide alternative prisms through which these rules and decisions can be assessed and re-thought by political actors. I show that, in relation to SOEs, the concepts ‘state and ‘act of state’ have been ascribed diverse meanings by adjudicators and other international actors, who have employed legal standards with divergent wording and thresholds when dealing with similar questions. I argue that the fragmented meaning of these terms should be understood, in part, as a result of the inherent malleability of these terms and the different expert vocabularies employed across regimes. It is exhibited that adjudicators in the international trade and investment regimes are more inclined towards piercing the corporate veil of SOEs, potentially evidencing the existence of biases against SOEs, which are perceived as inherently economically inefficient and politically motivated actors in an indiscriminatory manner. In the last chapter, I introduce alternative lines of thought regarding the regulation of SOEs in international law. I suggest that, instead of engaging in theoretical discussions on the proper delineation between the public and the private sector, it is more useful to focus on the distributional impact of international rules on various actors, especially on developing and emerging economies where the presence of SOEs is very high. Such alternative prisms of analysis open paths for future research and practice, with the goal of designing an international economic order that incentivises institutional experimentation in the pursuit of economic development and distributional equity.
Keywords: International Economic Law; International Investment Law; International law; International trade law; Public enterprises; State capitalism; State-owned enterprises

La protection des associés minoritaires : étude comparée de droit français et droit OHADA - Moundounga Mapangou, Ulrich (Université de Pau et des Pays de l'Adour, 2023)
La protection juridique des associés minoritaires se justifie en droit des sociétés et en droit OHADA par l’absence directe de la gestion des sociétés commerciales par ces derniers. De ce fait, les deux ordres juridiques mettent en œuvre plusieurs mécanismes afin de protéger les intérêts des minoritaires. Ces mécanismes sont de plusieurs natures à savoir des règles juridiques favorisant un traitement égalitaire de tous les associés ou des droits exclusifs aux associés minoritaires favorisant un équilibre de pouvoirs dans la gestion de la société mais également la coexistence d’acteurs capables de réguler le bon fonctionnement de la société, notamment le juge, les associations de défenses d’intérêts des associés minoritaires.Dans les sociétés où les enjeux économiques sont très importants comme les sociétés faisant appel public à l’épargne, les législateurs français et OHADA, soucieux de protéger les associés minoritaires, ajoutent au droit commun, l’intervention du droit des marchés financiers qui vient renforcer la protection des minoritaires, notamment dans l’exercice de leur droit de cession. Ainsi, l’on remarque que le droit des sociétés français et le droit OHADA utilisent quasiment les mêmes fondements juridiques pour protéger les associés minoritaires. Il existe plus de similitudes que des différences dans les deux ordres juridiques puis que le législateurs OHADA a entrepris une réforme en 2014 afin de renforcer considérablement les compétences des associés minoritaires dans la gestion de la société. Cette réforme du droit OHADA s’est quasiment rapprochée du droit de société.Toutefois, malgré les efforts du droit des sociétés français et du droit OHADA de protéger les intérêts des associés minoritaires, subsiste une précarité du statut des minoritaires. La loi de la majorité fait obstacle à ce que l’on puisse objectiver que la protection apportée aux associés minoritaires est absolument efficace. Pour en arriver à une protection efficace certains droits devraient être généralisés pour contrôler sereinement la gestion sociale et leurs intérêts. The legal protection of minority shareholders is justified in company law and in OHADA law by the direct absence of management of commercial companies by the latter. As a result, both legal systems implement several mechanisms to protect the interests of minority shareholders. These mechanisms are of several kinds, i.e. legal rules favouring equal treatment of all partners or exclusive rights for minority partners favouring a balance of power in the management of the company, but also the coexistence of actors capable of regulating the proper functioning of the company, in particular the judge, and associations defending the interests of minority partners.In companies where the economic stakes are very high, such as companies making public offerings, the French and OHADA legislators, anxious to protect minority shareholders, add to common law the intervention of financial market law, which reinforces the protection of minority shareholders, particularly in the exercise of their right to sell. Thus, it can be seen that French company law and OHADA law use almost the same legal basis to protect minority shareholders. There are more similarities than differences in the two legal orders since the OHADA legislators undertook a reform in 2014 in order to considerably strengthen the powers of minority shareholders in the management of the company. This reform of OHADA law has almost come close to company law.However, despite the efforts of French company law and OHADA law to protect the interests of minority shareholders, the status of minority shareholders remains precarious. The law of the majority prevents the protection of minority shareholders from being absolutely effective. To achieve effective protection, certain rights should be generalised in order to control the management of the company and their interests.
Keywords: Associé; Corporate law; Droit des sociétés; Droit des sociétés commerciales; Droits des associés; French law; Minoritaire; Minority; OHADA law; Ohada; Organisation pour l'harmonisation en Afrique du droit des affaires; Protection; Shareholders

The regulation of Corporate phoenix activity in South Africa - Basson, André Stephan (University of Johannesburg, 2023)
Phoenix activity involves conduct whereby a failing company (the old company) is replaced by a second company (the new company) in the operation of the same or a similar business and that involves the same or similar company controllers. Transactions of this nature can be legal and even be beneficial to society, since entrepreneurs who pursue a viable business may, if the new company succeeds, benefit the economy and many other stakeholders. These transactions are referred to as legal phoenix activity. Problems arise however when phoenix activity is engaged in with the goal of evading the debt of the old company, known as illegal phoenix activity. In other cases, even well-intentioned company controllers can cause significant harm by resurrecting a fundamentally flawed business. This conduct, although not illegal, is unduly prejudicial to stakeholders and is known as problematic phoenix activity. While this thesis focuses on illegal phoenix activity, several measures identified should also curb problematic phoenix activity. This study identifies the elements and common characteristics of illegal phoenix activity. It then analyses regulation pertaining to those elements and common characteristics with the aim of finding effective solutions to the problem. This includes evaluating measures that reverse prejudicial transactions that occur during illegal phoenix activity as well as holding complicit parties, such as company controllers and the new company, accountable for their actions. Regulation aimed at preventing and investigating illegal phoenix activity is also considered. This thesis uses the comparative legal approach to analyse regulatory responses to illegal phoenix activity. Australia, the United Kingdom, and the United States of America are examined. Several reported cases in South Africa involving what appear to be illegal phoenix activity are explored, along with the existing measures that are applicable to illegal phoenix activity in South Africa. A single anti-phoenix provision is undesirable as it has the potential to unjustifiably infringe on legal phoenix activity. This thesis proposes a multi-pronged approach, which involves a combination of better enforcement of existing laws and the introduction of smaller targeted amendments to legislation aimed at reducing the incidence illegal phoenix activity.
Keywords: ABUSE OF THE CORPORATE FORM; Bankruptcy fraud; Evasion of liability; Fraud on creditors; Phoenix activity; Phoenixism; Strategic bankruptcy; Successor liability; Transactions prejudicing creditors; Transfers at an undervalue

Kurumsal yönetim bakış açısıyla mali durumu bozulan anonim şirketlerde alacaklıların menfaatinin korunması - Demi̇rel Özdemi̇r, Duygu (Kocaeli Üniversitesi, 2023)
Anonim şirketler hukukunda alacaklılar, şirketlerin dış finansman kaynaklarının merkezini oluşturmakta ve bu nedenle de son derece önemli bir menfaat grubunu teşkil etmektedirler. Bu durum şirket alacaklılarının çıkarlarının etkin bir biçimde gözetilmesi ve korunmasını gerekli kılmaktadır. Zira alacaklıların alacaklarına kavuşabilmeleri için müracaat edebilecekleri tek kaynak şirketin malvarlığıdır. Dolayısıyla anonim şirketin mali durumunun bozulması sonucu malvarlığının kayba uğraması veya uğrama tehlikesi altında olması, alacaklıların menfaatlerini zedeleyici niteliktedir. Bu durum mali durumu bozulan anonim şirketlerde, alacaklıların menfaatlerinin gözetilmesini ve özellikle de öncül (ex-ante) koruma imkânlarıyla bu risk gerçekleşmeden önce bu konuda tedbirler alınmasını gerektirmektedir. Kurumsal yönetim anlayışı, anonim şirketlerde menfaat grupları arasındaki çıkar çatışmalarının en iyi, en adil şekilde dengelenmesini hedeflemektedir. Bu itibarla bu tez çalışmasında söz konusu menfaat çatışmaları özelinde kurumsal yönetimin şeffaflık, adillik, hesap verilebilirlik ve sorumluluk ilkeleri çerçevesinde bir menfaat grubu olarak şirket alacaklılarının menfaatlerinin, mali durumu bozulan veya bozulma tehlikesi altında olan anonim şirketlerde nasıl gözetilmesi ve korunması gerektiği hususunda bir bakış açısı sunulması hedeflenmektedir. Bu bakış açısından hareketle sermaye kaybı yaşayan, borca batık hale gelen anonim şirketlerin mali durumlarının iyileştirilmesi maksadıyla sermayenin korunması esası benimsenerek öngörülen TTK m.376 hükmü ile bu hükmün uygulanmasına ilişkin Tebliğ kapsamında öngörülen düzenlemelerin, alacaklıların menfaatlerinin korunması bakımından etkileri tartışılmaktadır. Ayrıca ilgili hükümlerin, şirketlerin mali yapılarının güçlendirilmesi bakımından yeterlilikleri ve yerindelikleri, karşılaştırmalı hukuk düzenlemeleri de göz önünde bulundurularak eleştirel bir bakış açıyla ayrıntılı şekilde incelenmektedir. Creditors are the key to external financing sources for companies under the statute of joint stock companies, and hence represent an important figure interest group. This situation needs the effective supervision and protection of the company's creditors' interests. This is because the company's assets are the only source to which creditors can turn to acquire receivables. Hence, the loss or threatened loss of the joint stock company's assets because of its worsening financial situation is detrimental to the creditors' interests. This circumstance necessitates that the interests of the creditors of companies with a worsening financial situation be considered and that steps be taken in this respect prior to the realization of this danger, particularly with ex-ante protection opportunities. The corporate governance method strives to achieve the most equitable resolution of conflicts of interest between interest groups in joint stock companies. This thesis aims to provide a perspective on how the interests of company creditors, as an interest group, should be observed and protected in joint stock companies whose financial situation deteriorates or is at risk of deterioration, within the framework of the principles of transparency, fairness, accountability, and responsibility of corporate governance. From this perspective, to improve the financial situation of companies that have capital loss and become over-indebted, the effects of the provisions of TCC art.376 and the Communiqué, which are envisioned based on the principle of capital maintenance, are discussed in terms of protecting the interests of creditors. In addition, the adequacy and suitability of the relevant rules in terms of strengthening the financial structures of corporations are analysed in depth from a critical standpoint, considering the norms of comparative law.
Tez N°789500
Keywords: Corporate governance; Creditors; Financial distress; Joint stock company

Anonim şirketlerde imtiyazlı paylar - Erten, Cengiz (Kocaeli Üniversitesi, 2023)
6102 sayılı Türk Ticaret Kanunu (TTK) ile Türk Ticaret Hukuku'nda özellikle anonim şirketler hukukunda yapılan değişiklikler arasında imtiyazlı paylarla ilgili düzenlemeler de bulunmaktadır. Mülga 6762 sayılı Türk Ticaret Kanunundaki (eTK) hükümlere benzerlik gösteren yönleri olsa da imtiyazlı paylarla ilgili daha ayrıntılı, yenilikler getiren ve önceki Kanun döneminde karşılaşılan sorunları gidermeye çalışan düzenlemelerin yapıldığı görülmektedir. TTK'daki imtiyazlı paylarla ilgili düzenlemelerin eTK döneminde ortaya çıkan sorunları giderip gidermediğinin ya da yeni sorunlara, belirsizliklere ve tartışmalara yol açıp açmadığının tespit edilerek değerlendirilmesi amacı bu tezin yazılmasına sebep oluşturmaktadır. Birinci bölümde önce genel olarak pay kavramı, imtiyazlı payın tanınması koşulları, imtiyaz kavramının terminolojik yönü ve mevzuatımızda konuyla ilgili düzenlemelerle hukuk sistemimize esin kaynağı olan yabancı hukuk sistemlerindeki düzenlemeler incelenmiştir. Ardından, imtiyaz tanınan hakların, eşitlik ilkesi, müktesep hak ve vazgeçilmez hak ile olan ilişkilerine değinilmiş ve imtiyazlı pay kavramının nasıl tanımlanması gerektiği üzerinde durulmuştur. Tezin asıl omurgasını oluşturan ikinci bölümde, imtiyaza konu haklar, malvarlığı hakları ve yönetim hakları olarak iki asıl eksen üzerinde incelenmiştir. İkinci bölüm için en fazla tartışılmış bulunan konu, yönetim haklarında imtiyaza ilişkindir. Yönetim haklarında imtiyazı oluşturan iki alt başlık, oy hakkında imtiyaz ve yönetim kurulunda temsilde imtiyaz ayrıntılı bir şekilde incelenmeye çalışılmış, imtiyazın kanundan kaynaklanan nedenlerle engellenmesinden bahsedilmiş ve diğer haklarda imtiyaza değinilmiştir. Tezin üçüncü bölümü imtiyazların korunması konusuna ayrılmıştır. Bu bölümde imtiyazlı pay sahipleri özel kurulunun (İPSÖK) yapısı, niteliği ve toplanması ile özel kurulun onayına bağlı kararlar halka açık olan ve olmayan şirketler dikkate alınarak açıklanmıştır. Üçüncü bölümde ayrıca İPSÖK kararlarına karşı açılacak iptal davalarıyla ilgili değerlendirmeler yapılmıştır. It is observed that although there are some similarities with the previous one, the new Turkish Commercial Code, Law No: 6102, introduces more detailed and innovative arrangements which is intended to provide an answer to the problems experienced during the abrogated code was in force in relation to preference shares. It is easily can be said that, by and large, the topic "preference shares" is the one of the most radically altered topic in the new code. The main purpose of this thesis is to shed light whether these innovative arrangements in the new code actually solving the problems that is intended to solve or, rather opposite, causing new problems and ambiguities. For this purpose, the first section of this thesis is allocated to analyse the concept of "share" in general and under which conditions the preference shares are granted first and then the meaning of the concept of "preference" is investigated. It is followed by subsections devised to identify the current domestic law, and comprative law that inspried the law makers in this area. In the following subsections it is attempted to explain where preference shares stand with respect to principle of equality, vested interests and inalienable rights, and how the concept of preference shares should be defined. In the second section, which constitutes the backbone of this thesis, the rights that are being subject of the preference shares are examined on the axis of the assest rights and the administrative rights. The topic of the administrative rights attached to preference shares is the most debated topic in this section. In this context under the head of the administrative rights, the issues related to priveleges in votes and the representation on the executive board are examined seperately in two separate subsections. Also in this subsection the issues of statutory basis of the prevention of preferences and the preferences in relation to other rights are grappled. The third section of the thesis is completely devised to the issues related to the protection of the preference shares. In this section the structure, qualifications, gathering of the board of preference shares owners and the decisions subject to approval of this board are explained in the context of private and public companies. In this section the suits that could be brought for the annulment of this board decision is evaluated briefly.
Tez N°818042
Keywords: Joint stock company; Preference Shares

Anonim ortaklıkta yönetim ve temsil yetkisinin devrinde yönetim kurulu üyelerinin hukuki sorumluluğu - Kalender, Süleyman (Çukurova Üniversitesi, 2023)
Anonim şirketlerde yönetim veya temsil yetkisi kural olarak yönetim kurulu tarafından kullanılmakla birlikte, özellikle halka açık veya büyük ölçekli ortaklıklarda söz konusu yetkilerin tamamının yönetim kurulu tarafından bizzat yerine getirilmesi uygulamada sık rastlanan bir durum değildir. Bu nedenle kanunda, yönetim kuruluna, yönetim veya temsil yetkisinin 6102 sayılı Türk Ticaret Kanunu' nun 367/I ve 370/II hükümlerinde yer alan şartlara uygun olarak, mevcut yönetim kurulu üyelerinden bir veya birkaçına yahut üçüncü kişilere devretmek suretiyle, şirketin yönetim teşkilatını belirleme yetkisi tanınmıştır. Şirket yönetimi konusunda uzmanlaşmış ve yeterli mesleki tecrübeye sahip olan kişilere yetkilerin devredilmesi, bir yandan şirkette profesyonelleşmeyi sağlamakta, diğer yandan kural olarak, devredilen yetkilerle birlikte bu kapsamda ortaya çıkabilecek hukuki sorumluluk da devredilmiş sayılacağından, yönetim kurulu üyelerinin hukuki sorumluluğunu sınırlandırmaktadır. Yönetim veya temsil yetkilerinin geçerli bir şekilde devredilmesi halinde, devredilen yetkilerle ilgili olarak yönetim kurulu üyelerinin hukuki sorumluluğu; murahhasların seçiminde, onlara verilecek talimatlarda ve murahhasların üst gözetiminde göstermeleri gereken makul derecede özen yükümlülüğü ile sınırlı olarak devam eder. Çalışmamızda, geçerli ve geçersiz yetki devri hallerinde, yönetim kurulu üyelerinin hukuki sorumluluğunun ne şekilde ortaya çıkacağı meselesi, mehaz İsviçre hukukundaki görüş ve yargı kararlarına yer verilmek suretiyle, detaylı bir şekilde incelenmiştir. Although the management or representation authority in joint stock companies is used by the board of directors as a rule, it is not common in practice that all of the said authorities are personally exercised by the board of directors, especially in publicly held or large-scale partnerships. For this reason, in the law, the board of directors is authorized to determine the management organization of the company by delegating the management or representation authority to one or more of the existing board members or to third parties in accordance with the provisions of the Turkish Commercial Code numbered 6102, 367/I and 370/II has been recognized. Delegation of powers to people who are specialized in company management and have sufficient professional experience, on the one hand, ensures professionalization in the company, and on the other hand, as a rule, legal responsibility that may arise in this context together with the delegated powers will be deemed to have been transferred, thus limiting the legal liability of the members of the board of directors. In case of a valid transfer of management or representation powers, the legal responsibility of the members of the board of directors regarding the delegated powers; limited to the reasonable care obligation that they must show in the selection of the executive directors, in the instructions to be given to them and under the supervision of the executive directors. In our study, the issue of how the legal responsibility of the members of the board of directors will arise in cases of valid and invalid delegation of authority has been examined in detail by including the opinions and judicial decisions in the Swiss law.
Tez N°832769
Keywords: Board of directors; Joint stock company